Painful Leg Ulceration in a Poorly Controlled Hypertensive Patient: A Case Report of Martorell Ulcer - Harsimran Kaur Malhi; Ali Didan; Stefan Ponosh; Sujith Prasad Kumarasinghe (Karger Publishers, 2017)
Martorell ulcer is a form of lower limb ulceration, preceded by a small area of excruciating pain. It often appears as a solitary lesion on the outer aspect of the lower limb, and is primarily associated with poorly controlled hypertension and diabetes. Treatment of the ulcer involves awareness and early correct diagnosis, adequate control of blood pressure, management of infection, and wound care. We describe a 77-year-old diabetic and hypertensive woman presenting with excruciating pain in her right lower lateral leg leading to a necrotic ulcer. Serial photographs of the evolution of the lesion and eventual healing of the ulcer are presented.